1005. Comparison of Weight Changes in Treatment-Naïve, HIV-Infected Patients Receiving Integrase Inhibitor-Based Therapy Versus Protease Inhibitor-Based Therapy. (31st December 2020) - Howe, Zachary; Farmer, Eric; Stevens, Brooke; Huesgen, Emily
Abstract: Background: Recent data regarding integrase inhibitor (INSTI) therapy indicate possible association with weight gain. The incidence and degree of weight gain seems to vary by both patient-specific and regimen-related factors, such as nucleoside reverse transcriptase (NRTI) backbone. Methods: This was a retrospective chart review of previously ART-naïve Indiana University Health LifeCare Clinic patients who started an INSTI- or PI-based regimens from 1/1/13 to 7/31/19. Adult patients without prior ART exposure receiving an INSTI- or PI-based regimen for at least 10 months were included. The primary objective was weight gain at 12 months after starting ART. Subgroup analyses were conducted by INSTI, PI, or NRTI backbone utilized. Statistical testing included Wilcoxon Rank-Sum Test and Chi Square analyses. Results: The patient population (N=162) was predominately male and African American with relative immunocompetence, generally achieving viral suppression after 12 months of ART. Patients receiving PI-based therapy were more likely to be Asian American or Hispanic (p=0.04), and to receive a tenofovir disoproxil fumarate (TDF)-based regimen (p=0.0034). No statistically significant difference in weight change was observed between INSTI- and PI-based regimens (median weight gain 5.1 kg vs 3.9 kg, p=0.52). The proportion of obese or overweight patients in the INSTI arm increased significantly as compared to baseline (p=0.00001). Subgroup analyses demonstrated significant increases in weight gain and clinically significant weight gain with tenofovir-based (tenofovir alafenamide and TDF) regimens compared to those with abacavir/lamivudine (p< 0.05). Primary Objective BMI Category Changes by INSTI or PI Agent NRTI Subgroup Analyses Conclusion: Lack of power makes meaningful interpretation of the results for the primary objective difficult. However, several of the prespecified secondary objectives and subgroup analyses demonstrated clinically significant results related to increased weight gain or BMI category changes with INSTI-, PI-, and tenofovir-based regimens. Checking the patient's weight at every appointment is considered standard practice at IU Health clinics, but missing values despite qualifying encounters were observed. Further commitment to standardized weighing practices should be a priority at clinics caring for patients living with HIV. Disclosures: All Authors : No reported disclosures